Enhancing Listening Skills with Popular Songs by Bruno Mars as The Teaching Media to English Foreign Learners - Amelia Dwi Setiyani; Entika Fani Prastikawati; Ajeng Setyorini (LPPM Universitas PGRI Semarang, 2026)
This study investigates the improvement of using songs by Bruno Mars as instructional media to enhance listening skills among English as a Foreign Language (EFL) learners at the senior high school level. The research employed a quantitative pre-experimental one-group pretest–posttest design involving 29 Grade X students selected through criterion-based purposive sampling. The instrument consisted of an objective listening comprehension test measuring word recognition, listening for specific information, and general comprehension. The data were analyzed using the Shapiro–Wilk normality test and a paired-sample t-test. The findings reveal a significant improvement in students’ listening performance, with the mean score increasing from 60.07 in the pre-test to 80.52 in the post-test. The paired-sample t-test result (t(28) = 14.024, p < 0.05) indicates a statistically significant difference between pre-test and post-test scores, confirming the effectiveness of song-based instruction. The improvement is theoretically supported by Krashen’s Language Acquisition Theory, particularly the concepts of comprehensible input and affective filter, as well as bottom-up and top-down listening processes. The consistent exposure to the English in Bruno Mars songs contributed to enhanced phonological awareness and accent familiarity, which are essential components in EFL listening development. These findings suggest that accent-aligned popular songs, when integrated with structured listening activities, can serve as an effective pedagogical strategy to improve students’ listening comprehension in secondary-level EFL classrooms.